Rationale and design of a screening study to detect schistosomiasis‐associated pulmonary hypertension in Ethiopia and Zambia. (22nd April 2022) - Sinkala, Edford; Ahmed, Hanan Yusuf; Sibomana, Jean Pierre; Lee, Michael H.; Kassa, Biruk; Kumar, Rahul; Mazimba, Sula; Binegdie, Amsalu B.; Mpisa, Sydney; Wamundila, Kawana; Graham, Brian B.; Hilton, Joan F.
Abstract: Schistosomiasis is a major cause of pulmonary arterial hypertension (PAH) worldwide, but the prevalence and risk factors for schistosomiasis‐associated PAH (SchPAH) development are not well understood. Schistosomiasis‐associated hepatosplenic disease (SchHSD) is thought to be a major risk factor for PAH development. Herein, we describe our plans for prospectively screening SchHSD subjects for clinical evidence of PAH at two major academic medical centers and national referral hospitals in Addis Ababa, Ethiopia and Lusaka, Zambia. The screening study will primarily be conducted by echocardiography, in addition to clinical assessments. Plasma samples will be drawn and banked for subsequent analysis based on preclinical animal model rationale. If successful, this study will demonstrate feasibility of conducting prospective cohort studies of SchPAH screening in schistosomiasis‐endemic regions of Africa, and provide initial data on clinic‐based disease prevalence and potential mechanistic biomarkers underlying disease pathogenesis.